The Effect Of Pop-Up Advertising And Perceived Intrusiveness On Brand Awareness And Advertising Avoidance With Advertising Value As A Moderation Factor (Study On Youtube Users) - Gana Bisatya, Sanggya; Made Sukresna, I (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This study aims to determine the effect of pop-up advertising on perceived intrusiveness, the effect of perceived intrusiveness on brand awareness, the influence of advertising on ad avoidance, and the role of advertising value on ad avoidance among YouTube users. Primary data is the data used in this research, obtained from questionnaire data on 120 YouTube users in Semarang city. The method of data analysis used is the Partial Least Square (PLS) analysis tool. The results of the study show that Pop-up Ads have a positive and significant effect on Perceived Intrusiveness with an original sample value of 0.311 and a pvalue of 0.000, a standard error value of 0.080 where this value is smaller than the path coefficient of 0.311. Perceived intrusiveness has a positive and significant effect on ads avoidance with an original sample value of 0.648 and a p-value of 0.000, a standard error value of 0.068, which is smaller than the path coefficient of 0.648. Perceived Intrusiveness has a positive and significant effect on brand awareness with an original sample value of 0.351 and a p-value of 0.000, a standard error value of 0.086 which is smaller than the path coefficient of 0.351. Perceived intrusiveness has a positive and significant effect on ads avoidance with advertisement value as a mediating variable with an original sample of 0.052 and a pvalue of 0.000, a standard error value of 0.023 where this value is larger than the path coefficient of 0.052. (P-value <0.05). Data processing proves that pop-up advertisements simultaneously affect perceived intrusiveness, perceived intrusiveness simultaneously influences brand awareness, advertisements simultaneously influences advertising avoidance, and Perceived Intrusiveness simultaneously influences ads avoidance with advertisement value as a mediating variable. Advertisers can use this research as a reference in placing pop-up ads so as not to suffer losses caused by internet users who do not care about the ads that appear.